Conservatism and “copy-if-better” in chimpanzees (Pan troglodytes) - van Leeuwen, Edwin J. C.; Call, Josep (Animal cognition, 2017)
Social learning is predicted to evolve in socially living animals provided the learning process is not random but biased by certain socio-ecological factors. One bias of particular interest for the emergence of (cumulative) culture is the tendency to forgo personal behaviour in favour of relatively better variants observed in others, also known as the “copy-if-better” strategy. We investigated whether chimpanzees employ copy-if-better in a simple token-exchange paradigm controlling for individual and random social learning. After being trained on one token-type, subjects were confronted with a conspecific demonstrator who either received the same food reward as the subject (control condition) or a higher value food reward than the subject (test condition) for exchanging another token-type. In general, the chimpanzees persisted in exchanging the token-type they were trained on individually, indicating a form of conservatism consistent with previous studies. However, the chimpanzees were more inclined to copy the demonstrator in the test compared to the control condition, indicating a tendency to employ a copy-if-better strategy. We discuss the validity of our results by considering alternative explanations and relate our findings to the emergence of cumulative culture.